ANTECEDENTS OF CUSTOMER CITIZENSHIP BEHAVIOR AMONG AUTOMOBILE ONLINE BRAND COMMUNITY IN MALAYSIA - Aishah, Siti Noor; Shaari, Hasnizam (Journal of Technology Management and Business, 2017)
This study intends to explore the antecedents of customer citizenship behavior (CCB) in Malaysia. CCB has been frequently debated in the last few decades, but researchers have not reached consensus on the definitions of various extra-role behavior because due to the inconsistent terminologies of CCB. The systematic sampling among 156 members of automobile online brand communities revealed that brand trust and brand love has a significant relationship on customer citizenship behavior. Â